AI AS A COGNITIVE PROSTHESIS: DOES EDUCATIONAL AI REDUCE INTELLECTUAL AUTONOMY? - Komang Ayu Shri Candrika Kumara; Ida Bagus Ari Arjaya; Desak Nyoman Budiningsih; Viony Aprilia Agustina (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
The rapid integration of generative artificial intelligence (AI) in education has positioned AI not merely as a technological tool, but increasingly as a cognitive prosthesis that extends learners’ cognitive capacities. While AI-driven systems offer substantial benefits—such as personalized learning, scaffolding, enhanced metacognitive regulation, and instructional efficiency—concerns persist regarding cognitive offloading, diminished critical thinking, reduced intellectual autonomy, and ethical risks. This study aims to critically examine the dual role of generative AI as a cognitive prosthesis in learning by synthesizing recent empirical and theoretical literature. Employing a systematic literature review methodology, this study analyzes peer-reviewed articles and proceedings indexed in Scopus and Copernicus published between 2015 and 2025. The reviewed studies are organized into two thematic domains: (1) the advantages and limitations of generative AI as a cognitive prosthesis in learning, and (2) the evolving roles of teachers and students in AI-mediated educational environments. The findings indicate that while generative AI can enhance metacognitive skills, creativity, learning efficiency, and personalized instruction, excessive dependence may lead to cognitive laziness, surface learning, weakened critical thinking, and ethical challenges related to data privacy and academic integrity. The study concludes that generative AI should be positioned as a supportive cognitive partner rather than a replacement for human cognition. Effective integration requires strong pedagogical design, ethical governance, and active mediation by educators to ensure that AI enhances learning without undermining intellectual autonomy.